Research Progress on the Effects of Main Components in Flour on the Quality of Steamed Bread - WANG Xin-yu; HAN Yan-fang; LI Yan; GUO Zi-xuan; HUAN Mei-li; REN Chen-gang (Liang you shipin ke-ji, 2021)
The quality of steamed bread is not only related to the formula and production technology of steamed bread,but also in connection with the quality of flour.With the development of society and the improvement of people's living standards,the advantages of special flour for steamed bread have become increasingly prominent.In this paper,the effects of starch,protein,lipid and ash in flour on the quality of steamed bread were reviewed to provide theoretical support for the production of high-quality steamed bread flour and the production of high-quality steamed bread.